Globalisation, models of competitive advantage and skills - Keep, E; Maynew, K (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2001)
This paper examines a profound paradox in current thinking on the process of globalisation. The paradox is this: many commentators, particularly those living in Anglo-Saxon countries, see one of the main likely outcomes of globalisation as being the triumph of the Ango-Saxon business model of shareholder value capitalism and its dominance over other models of capitalism. At the same time, there is a widespread belief that high levels of skill and advanced people management system that embraces high performance methods of organising work will be the key to business success in the 21st century. However, a considerable body of research indicates that the Anglo-Saxon model of management, coupled with its interaction with financial systems and consumer markets, renders it extremely difficult to adopt this high performance workplace model or to invest in high levels of skill for the bulk of the workforce. This paper explores these issues. It looks at the degree to which globalisation has come to be associated with the spread of the Ango-Saxon business model; and examines the parallel model of the high performance, high skill workplace, adoption of which bodies such as the OECD have suggested is the only means of securing competitiveness in a globalised economy. The paper then explores the central paradox, that the high performance, high skills model is apparently hard to nurture within an Anglo-Saxon business environment, and seeks to suggest why many UK firms find it hard to do what they are repeatedly told is good for them. The final section suggests some possible consequences, in terms of both what impact adoption of the Ango-Saxon model might have on the skills and IR systems of other developed countries, and, conversely, what impact their adoption and modification of selected elements of the Anglo-Saxon business model might have on the UK and USA.